2015
DOI: 10.1103/physrevapplied.4.024010
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Magnetic States in Circular Thin-Film Nanomagnets with Large Perpendicular Magnetic Anisotropy

Abstract: The scaling of the energy barrier to magnetization reversal in thin film nanomagnets with perpendicular magnetization as a function of their lateral size is of great current interest for high-density magnetic random access memory devices. Here we determine the micromagnetic states that set the energy barrier to thermally activated magnetization reversal of circular thin film nanomagnets with large perpendicular magnetic anisotropy. We find a critical length in the problem that is set by the exchange and effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 21 publications
(24 reference statements)
4
51
0
Order By: Relevance
“…Thus far, STT-MRAM devices are larger than this scale. Recent experiments on large arrays of very uniform magnetic bits have found that the energy barrier (for fixed element thickness) scales with the element diameter (not the diameter squared) [146], consistent with the predictions of a recent micromagnetic model [144] and the reversal mode pictured in figure 19(b).…”
Section: Department Of Physics New York Universitysupporting
confidence: 58%
See 2 more Smart Citations
“…Thus far, STT-MRAM devices are larger than this scale. Recent experiments on large arrays of very uniform magnetic bits have found that the energy barrier (for fixed element thickness) scales with the element diameter (not the diameter squared) [146], consistent with the predictions of a recent micromagnetic model [144] and the reversal mode pictured in figure 19(b).…”
Section: Department Of Physics New York Universitysupporting
confidence: 58%
“…However, the device response clearly indicates more complex behaviour with intermediate multi-domain states (illustrated schematically in figure 19(b)), even in the switching of 50 nm diameter magnetic elements [143][144][145]. Further, thermal fluctuations play an important role in the dynamics, which can aid the switching process (e.g.…”
Section: Department Of Physics New York Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…For a given MTJ stack, the switching voltage is practically independent from the device size and shape in our interval of investigated sizes (not shown). This finding is consistent with the consensual conclusion that the switching energy barrier is almost independent from the device area 38,39 for device areas above 50 nm. In spite of this quasi-independence of the switching voltage and the device size, the switching duration was found to strongly depend on device size (Fig.…”
Section: B Switching Resultssupporting
confidence: 92%
“…Using 42 , the domain wall stiffness field can be estimated to be at the most 20 mT in our devices. In circular devices, the domain wall has to elongate upon its propagation 38 such that the domain wall stiffness field H DW depends in principle on the DW position. It should be maximal when the wall is along the diameter of the free layer.…”
Section: Switching Model: Domain Wall-based Dynamicsmentioning
confidence: 99%